اختبار طريقة تخمين الحركة كائنية التوجه المتناظرة في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة من أجل أنماط مختلفة للحركة - القبيلي, مثنى; حاتم, إياد; شعلال, ياسين; جبيلي, ثناء (Latakia University Journal -Engineering Sciences Series, 2018)
Video signals have become an essential part of our everyday life. Major efforts have been done to develop systems and networks to support video applications. However, video processing is a resource-demanding task mainly in motion estimation stage. Therefore, classical motion estimation algorithms do not fit constricted resource systems such as wireless multimedia sensor networks. In this paper, we consider SYMO-ME which is a symmetric-object oriented motion estimation approach in wireless multimedia sensor networks. It reduces the high complexity of motion estimation process by taking into consideration frame objects properties and shapes. It aims to save sensors energy and other resources by exploiting the symmetry property of video frames objects. Based on adaptability criterion, we offer a novel classification of fast block matching algorithms. Three different SYMO-ME based block matching motion estimation algorithms are implemented. We compared and evaluated those algorithms under different motion modes and analyzed the impact of both search range and block size parameters. Performance evaluation of several extensive simulations is done via three basic evaluation metrics reflecting efficiency of motion estimation algorithm, energy cost, and video quality غدت الإشارات الفيديوية جزءاً أساسياً من حياتنا اليومية، وكرست الجهود الحثيثة لتطوير مختلف الأنظمة والشبكات بهدف دعم تطبيقات الفيديو. لكن تعد معالجة المعطيات الفيديوية مهمةً معقدةً وبالغة المتطلبات خاصةً فيما يتعلق بمرحلة تخمين الحركة. حيث أن الخوارزميات التقليدية لتخمين الحركة لا تلائم الأنظمة محدودة الموارد كما هو الحال في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة. يركز هذا البحث على الطريقة SYMO وهي طريقة كائنية التوجه لتخمين الحركة بين الإطارات الفيديوية المتعاقبة في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة. تخفض SYMO من تعقيد مرحلة تخمين الحركة فهي تأخذ بالحسبان خصائص أشكال الكائنات في الإطارات الفيديوية فتحافظ على طاقة وموارد العقد الحساسة من خلال استغلال خاصية التناظر لتلك الكائنات. واعتماداً على درجة التكيف في أسلوب تخمين الحركة، يعرض البحث تصنيفاً جديداً لخوارزميات تخمين الحركة ويهدف إلى اختبار ثلاث خوارزميات، من أصناف مختلفة، اعتماداً على الطريقة كائنية التوجه. ويشمل تقييم الأداء ثلاثة محددات أساسية تعكس كفاءة خوارزمية تخمين الحركة، واستهلاك الطاقة، وجودة المعطيات الفيديوية وذلك تحت أنماط مختلفة من الحركة إضافة إلى دراسة وتحليل أثر تغيير معاملي تخمين الحركة المتمثلين في مجال البحث وحجم كتلة البكسلات المستخدم.